The Concepts of TRUTH and LIE in Lithuanian, Polish and English Proverbs: A Comparative Analysis - Snukiškienė, Irena (Tautosakos darbai, 2026)
In cultural linguistics, proverbs and proverbial sayings serve as textual data, offering a diachronic view: being old, popular among various layers of society and repetitive, they reflect and shape a nation’s culture, stereotypes and axiological system, and are thus considered a great tool for the analysis of a society’s linguo-cultural worldview. This article aims to compare the conceptualisation of TRUTH and LIE in Lithuanian, English and Polish proverbs. The data consist of proverbs with the keywords truth and lie, selected from the main Lithuanian, English and Polish proverbial collections: the Card Index of Lithuanian Proverbs and Proverbial Phrases kept at the Institute of Lithuanian Literature and Folklore, The Oxford Dictionary of English Proverbs, A Dictionary of American Proverbs, and Nowa Księga przysłów polskich (A New Book of Polish Proverbs). The analysis was carried out by applying the qualitative methodology of the Ethnolinguistic School of Lublin by extracting semantic aspects of the concepts analysed, seen from specific interpretative perspectives, and grouping them into semantic profiles. The study reveals the semantic and axiological content of the concepts analysed in all three languages and concentrates mainly on comparison.